2016
DOI: 10.1111/dmcn.13360
|View full text |Cite
|
Sign up to set email alerts
|

Environmental impact on young children's participation in home‐based activities

Abstract: AIM To test the effect of child, family, and environmental factors on young children’s participation in home-based activities. METHOD Caregivers of young children were recruited using convenience and snowball sampling. Participants were 395 caregivers of children aged from 1 month to 5 years and 11 months. Demographic items and the home section of the Young Children’s Participation and Environment Measure were administered online, followed by completion of the daily activities, mobility, and social/cognitive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
47
0
6

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(58 citation statements)
references
References 25 publications
5
47
0
6
Order By: Relevance
“…This measure yields normative scores in four domains: daily activities, social/cognitive, mobility, and responsibility. 17,21 Hence, for this study, we computed a dichotomous PEDI-CAT score, using a 10th percentile cut-off point based on the scaled score for the daily activities domain. 20 Previous studies with a mixed sample of children with and without disabilities have established small to moderate associations between Young Children's Participation and Environment Measure home involvement scores and children's PEDI-CAT norm scores for daily activities, and a significant indirect effect of PEDI-CAT daily activities norm scores on home involvement.…”
Section: Child Demographics Functional Status and Functional Capabimentioning
confidence: 99%
See 1 more Smart Citation
“…This measure yields normative scores in four domains: daily activities, social/cognitive, mobility, and responsibility. 17,21 Hence, for this study, we computed a dichotomous PEDI-CAT score, using a 10th percentile cut-off point based on the scaled score for the daily activities domain. 20 Previous studies with a mixed sample of children with and without disabilities have established small to moderate associations between Young Children's Participation and Environment Measure home involvement scores and children's PEDI-CAT norm scores for daily activities, and a significant indirect effect of PEDI-CAT daily activities norm scores on home involvement.…”
Section: Child Demographics Functional Status and Functional Capabimentioning
confidence: 99%
“…On the basis of previous studies, 16,17 we also expected child functional abilities and environmental factors to significantly predict participation. Given the significant amount of time children and adolescents spend in their homes, particularly during recovery from critical illness, the primary objectives of this study were to explore change in home participation frequency and involvement of critically ill children over the first 6 months after discharge (aim 1) and to identify child, service, and environmental factors that predict participation frequency and involvement change in the home setting (aim 2).…”
mentioning
confidence: 99%
“…However, as the ICF-CY biopsychosocial paradigm of health and functioning theorizes, the environment has shown to play a vital role in explaining children's participation levels (Anaby et al, 2014;Albrecht and Khetani, 2016;Guichard and Grande, 2017;Di Marino et al, 2018). Environmental factors interact with all components of functioning and provide an assessment of the physical, social, and attitudinal impact of barriers and supports to participation.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have emphasized the role of environmental factors in the participation of pre-school-and school-aged children in everyday life situations (Anaby et al, 2014;Albrecht and Khetani, 2016;Guichard and Grande, 2017;Di Marino et al, 2018). Results showed that child characteristics (namely child functioning, the presence of disability, functional limitations, or complexity of the child's condition) had an indirect effect on participation in home, school, or community activities through perceived environmental barriers or supports by parents.…”
Section: Faculty Of Psychology and Educational Sciences University Omentioning
confidence: 99%
See 1 more Smart Citation